THE HEALTH STATUS OF A RURAL IRANIAN COMMUNITY IN THE CASPIAN LITTORAL AREA IN 1976 - Ali A.Alemi; F.Shafii; P.Kamali (Tehran University of Medical Sciences, 1978)
The health status of the rural community under the study is measured in terms of vital statistics, and living conditions in relation to demographic data. The findings reveal that this rural population can be considered a very unhealthy one. For instance, the infant mortality rate is 98.4 per 1000 live births, and 80.0 per cent of the total population were found to be infected by one or more parasitic diseases. Allocation of resources has been recommended to raise the standard of living, in order to bring about a better hygienic environment. Accessibility of health services through expansion of primary health care, and in this sphere the use of health auxiliaries should yet again receive special consideration.